2008
DOI: 10.1111/j.1460-9592.2007.02390.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of rocuronium‐induced withdrawal movement in children: a comparison of remifentanil with alfentanil

Abstract: Both remifentanil 1 microg.kg(-1) and alfentanil 15 microg.kg(-1) can be used to prevent rocuronium-associated withdrawal movement in children because they are equally effective and attenuate the increase in MAP and HR after intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Remifentanil 1 or 0.5 lg/kg was already known to be effective in preventing rocuronium-induced withdrawal movement [15]. The incidence of withdrawal movements was reduced further with remifentanil at 1 lg/kg compared with that at 0.5 lg/kg.…”
Section: Discussionmentioning
confidence: 96%
“…Remifentanil 1 or 0.5 lg/kg was already known to be effective in preventing rocuronium-induced withdrawal movement [15]. The incidence of withdrawal movements was reduced further with remifentanil at 1 lg/kg compared with that at 0.5 lg/kg.…”
Section: Discussionmentioning
confidence: 96%
“…Although the higher dose of alfentanil could improve the intubation conditions of the control group in children, we have been concerned about hemodynamic instability and chest wall Values are expressed as mean ± SD T0, baseline (before induction); T1, after test drug (ketamine or saline) injection; T2, after alfentanil injection; T3, before intubation; T4, 1 min after intubation; T5, 3 min after intubation * P \ 0.05, versus control group P \ 0.05, versus baseline values (T0) within the group rigidity before tracheal intubation during sevoflurane induction with higher doses. In a previous study, the higher dose of alfentanil (15 lg/kg) was reported to cause significant decrease in MAP and HR before intubation during propofol induction in children [19]. Further studies exploring the effect of ketamine in improving intubation conditions and hemodynamic instability during sevoflurane induction with the higher doses of opioids without muscle relaxant are justified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, remifentanil can prevent the withdrawal response associated with rocuronium injection. 17 A retrospective review of 287 cases of rigid bronchoscopic FBA removal showed incidence rates of adverse events related to anesthesia and surgery were 0.7% and 7.6%, respectively. 10 The most common adverse event related to anesthesia was laryngospasm.…”
mentioning
confidence: 99%